Assessment of vitamin D status in turkish adolescents: its relation to obesity, cardiometabolic risk factors and nutritional status - (:unkn) unknown (MATTIOLI 1885, 2019)
Studies on effects of vitamin D on human body have indicated that vitamin D deficiency may contribute to an increased risk of obesity and cardiometabolic risk factors; during childhood; however, these relationships remain unclear. The aim of this study is to determine the influences of adiposity, dietary and environmental factors on vitamin D status and the relationship between 25(OH)D and cardiometabolic risk factors in adolescents. The research was carried out in 69 adolescents (60.9% female, 39.1% male) who applied to the Istanbul Marmara University Pendik Educational Research Hospital Pediatric Endocrinology Department, aged between 12 and 17 years. Data was collected in three stages; in the first stage, the questionnaire was developed including the demographic status, nutritional status and physical activities of those adolescents. In the second stage, anthropometric measurements were taken. In the third and final stage, biochemical analysis was measured. There were no statistical differences between groups (Vitamin D deficient and sufficient) in dietary and environmental factors that may have affected serum 25(OH)D. Serum 25(OH) D level was not inversely correlated with anthropometric measurements (p>0.05). While there were no significant differences between serum 25(OH)D levels and HOMA-IR; there was a positive correlation between serum calcium and HOMA-IR (r=0.276, p<0.05) independent of body adiposity There was a positive correlation between serum 25(OH)D levels and amount of daily dietary protein (r=0.344) and fat intake (r=0.286) (p<0.05), but there was no correlation between serum 25(OH)D and dietary vitamin D and calcium intake (r=-0.022, r=0.235; respectively). Because foods are not primary sources of vitamin D, this correlation should be assessed with further research on population who consume fortificated food. The results from this study suggest the importance of vitamin D supplementation and food fortification in Turkish adolescents. This study didn't show relationship between vitamin D status and obesity, insulin resistance. Effects of vitamin D deficiency on chronic diseases need to be assessed with prospective studies.
Keywords: Adolescent; Insulin Resistance; Obesity; Vitamin D; HOMEOSTASIS MODEL ASSESSMENT; D DEFICIENCY; INSULIN-RESISTANCE; HEALTHY-CHILDREN; SENSITIVITY; PREVALENCE; GLUCOSE